1987
DOI: 10.1093/nar/15.18.7249
|View full text |Cite
|
Sign up to set email alerts
|

Processing of precursor RNAs from mitochondria ofNeurospora crassa

Abstract: Neurospora mitochondrial DNA is transcribed into long molecules containing the information of several genes. Processing leads to formation of functionally active RNAs. It has been shown previously that when tRNA sequences are present in these transcripts excision of mRNAs occurs at the acceptor stem of these tRNA sequences. We have investigated the processing of precursor RNAs transcribed from a region of the mitochondrial genome devoid of tRNA genes. This region comprises the genes encoding subunit 6 of the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1989
1989
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…However, only the larger 2?3 kb transcript was notably overexpressed at 37˚C. The existence of both pre-processed and processed forms of mitochondrial mRNAs, including the COX1 transcript, has been described previously in several fungi (Agsteribbe & Hartog, 1987;Burger et al, 1985;Costanzo & Fox, 1990;Dyson et al, 1989;Grivell, 1989;Osinga et al, 1984;Tracy & Stern, 1995), plants (Barkan, 1988;Gray & Lovello, 1993;Tracy & Stern, 1995;Wolff & Kuck, 1996) and animals (Ojala et al, 1980;Tracy & Stern, 1995). These pre-processed or precursor RNAs comprise polycistronic transcripts that have not yet been processed into smaller, intermediate and mature forms of RNA.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…However, only the larger 2?3 kb transcript was notably overexpressed at 37˚C. The existence of both pre-processed and processed forms of mitochondrial mRNAs, including the COX1 transcript, has been described previously in several fungi (Agsteribbe & Hartog, 1987;Burger et al, 1985;Costanzo & Fox, 1990;Dyson et al, 1989;Grivell, 1989;Osinga et al, 1984;Tracy & Stern, 1995), plants (Barkan, 1988;Gray & Lovello, 1993;Tracy & Stern, 1995;Wolff & Kuck, 1996) and animals (Ojala et al, 1980;Tracy & Stern, 1995). These pre-processed or precursor RNAs comprise polycistronic transcripts that have not yet been processed into smaller, intermediate and mature forms of RNA.…”
Section: Discussionmentioning
confidence: 68%
“…This common occurrence of transcriptional units in mitochondrial DNA from a variety of plants (Barkan, 1988;Tracy & Stern, 1995;Wolff & Kuck, 1996) and fungi (Agsteribbe & Hartog, 1987;Burger et al, 1985;Costanzo & Fox, 1990;Dyson et al, 1989;Grivell, 1989;Osinga et al, 1984;Tracy & Stern, 1995) implicates their role in facilitating the co-ordinate regulation of gene expression. In our study, the overexpression of a single transcriptional unit encoding ATP9, COX1 and ATP8 mRNAs in C. neoformans suggests that at elevated host temperatures the serotype A strain (H99) upregulates expression of this transcriptional unit.…”
Section: Discussionmentioning
confidence: 94%
“…The three genes CO-III, ATPase-6 and ND-3 are linked closely in the mitochondrial genome, 17 and posttranscriptional processing is necessary to produce mature protein-encoding genes. 23 The precursor mitochondrial transcript containing CO-III, ATPase-6, and ND-3 has been demonstrated in human tissue. 24 In our study, CO III, ATPase-6, and ND-3 were shown to be contained in a precursor mRNA species and downregulated by 400-lux light rearing.…”
Section: Discussionmentioning
confidence: 99%
“…In Neurospora, Aspergillus and Schizosaccharomyces mitochondria, polycistronic transcripts were found to be processed by tRNA excision and additional processing events, generating mono-or dicistronic RNA species (e.g. [26,16,14,1,45,8]). In Kluyveromyces and Saccharomyces, multiple promoters exist for several small transcriptional units [63,22], and processing occurs by endonucleolytic cleavage close to tRNAs or at conserved sequence motifs [60,12].…”
Section: Polycistronic Transcripts Undergo Substantial Processing Eventsmentioning
confidence: 99%
“…For example, compact animal mtDNAs are transcribed into precursor molecules, which subsequently are processed to monocistronic RNAs by excision of individual tRNAs [58,59]. A similar mode of RNA processing seems to be employed in mitochondria of Aspergillus and Neurospora, where tRNA are used as processing signals [16,14,1,26 ]. However, mitochondrial DNA from the yeast Saccharomyces cerevisiae carries multiple transcription units, which are controlled by their own promoters [22].…”
Section: Introductionmentioning
confidence: 99%